CuMn2O4/chitosan micro/nanocomposite: Green synthesis, methylene blue removal, and study of kinetic adsorption, adsorption isotherm experiments, mechanism and adsorbent capacity - Malihe Samadi Kazemi; Azam Sobhani (Arabian Journal of Chemistry, 2023)
In this work, we choose a simple, green hydrothermal method for the fabrication of a pure phase of CuMn2O4 nanostructures in the presence of onion as a capping agent, for the first time. In the next step, we synthesized CuMn2O4/chitosan micro/nanocomposite. The structural analysis of nanostructures and composites showed their purity. The results showed that the prepared micro/nanocomposites have very efficient adsorption for removing methylene blue. In order to design and analyze the experiments were used response surface methodology (RSM). In the optimal conditions, the pH value, adsorbent dose, initial concentration, contact time and stirring speed obtained 6.5, 1.25 g/L, 1 mg/L, 5 min and 500 rpm respectively. Kinetic adsorption and adsorption isotherm experiments were used to investigate the process mechanism and adsorption capacity of CuMn2O4/chitosan composites for methylene blue, for the first time. The value of R2 (0.997) and the qe cal which was close to the qe exp, confirmed the pseudo-first-order kinetic model. Langmuir isotherm model with a qmax of 54.05 mg/g described the experimental data well. KL in this model obtained 0.06, which was in the range of 0–1, which means the adsorption process CuMn2O4/chitosan composite for methylene blue was favorable. Moreover, the present adsorbent can be effectively used up to five adsorption/desorption cycles.